Percobaan Produksi Biogas dari Kotoran Sapi dan Kotoran Ayam dengan Penambahan Enzim Papain - Zulfikar Ali As; Hardiono Hardiono; Syarifudin A. (Poltekkes Kemenkes Banjarmasin Jurusan Kesehatan Lingkungan Banjarbaru, 2014)
Production of Biogas from Cow Manure and Chicken Manure with Addition of Papain. Farms not only contribute positively to meet the demands of protein and increase incomes but also have a negative impact on the environment due to their wastes, especially manure. Biogas produced from the anaerobic decomposition of organic waste is a solution of manure utilization to be a fuel which is cheap and environmentally friendly. To accelerate the production of biogas it is needed a proteoloitik enzyme from papaya, which is called papain. This study aims to calculate the production of biogas from cow manure and chicken manure with addition of papain. The experiments were conducted in the digester made from plastic drums and observed for 30 days. The results showed that the papain influenced of production acceleration of biogas from cow manure. Comparison of biogas production in a week from cow manure: cow manure + 2 kgs of papaya pieces: cow manure + 4 kgs of papaya pieces are 202.7 liters: 263 liters: 332.3 liters. Cow manure did not need other ingredients except water with ratio 1: 1½ . Chicken manure had not been able to produce biogas because their CN ratio was not eligible, although the chaff had been added to increase the carbon content. Biogas from cow manure with addition of papain can be applied on a wider scale, while biogas from chicken manure requires other ingredients that biodegrade easier to add C content in the mixture. Keywords : biogas; cow manure; chicken manure; papain